2023
DOI: 10.24996/ijs.2023.64.10.15
|View full text |Cite
|
Sign up to set email alerts
|

Response of Two Rosa sp. to Light Quality in Vitro.

Layth Sareea Al-Rekaby

Abstract: In this study, dark and various light qualities (white, red, green, and blue) were applied to evaluate their effects on growth characteristics, chemical content, and callus characteristics of Rosa damascene Mill. and Rosa hybirda L.    Explant (single-node and shoot tips) cultured on MS media supplemented with sucrose, agar, and plant growth regulators ( Kin 0.5 mg/l and IBA 1 mg/l for whole plant formation experiment or 1 mg/l kin with 0.5 mg/l IBA for callus experiment), incubated in a growth chamber.    The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…For Al-Taif rose, a combination of blue + red light (1:2) was found to increase the root length and the number of roots while cool white + warm white (1:1) resulted in 100% rooting. Taken together, these results confirm previous findings in other rose species, including Rosa chinensis [43], Rosa canina [46], Rosa damascena, and Rosa hybrida [47].…”
Section: Effect Of Medium Salt Strength Sucrose Concentration and Lig...supporting
confidence: 92%
See 1 more Smart Citation
“…For Al-Taif rose, a combination of blue + red light (1:2) was found to increase the root length and the number of roots while cool white + warm white (1:1) resulted in 100% rooting. Taken together, these results confirm previous findings in other rose species, including Rosa chinensis [43], Rosa canina [46], Rosa damascena, and Rosa hybrida [47].…”
Section: Effect Of Medium Salt Strength Sucrose Concentration and Lig...supporting
confidence: 92%
“…They found that an RB (i.e., 50% red and 50% blue) treatment significantly increased the number of roots per plant (i.e., 3.9). More recently, Al-Rekaby [47] pointed out that the highest values for several rooting parameters (i.e., root length, the number of roots, and fresh and dry root weight) for Rosa damascena and Rosa hybrida occurred when cultured under red light. Blue and red light are the most efficiently absorbed by chlorophyll during photosynthesis [48].…”
Section: Effect Of Medium Salt Strength Sucrose Concentration and Lig...mentioning
confidence: 99%